KEEFEKTIFAN PELAKSANAAN RINTISAN CORPORATE FARMING (Studi Kasus Gapoktan Tani Mandiri, Kecamatan Tawangsari) - Yusrina Luthfi Hanifah; Sapja Anantanyu; Eksa Rusdiyana (AGRORADIX : Jurnal Ilmu Pertanian, 2023)
Agricultural development can be supported by agricultural innovation, through the development of modern agricultural clusters corporate farming (CF) based, it has been implemented by the Tani Mandiri Farmer Group Association in 2018 on 28 hectares of land belonging to 4 farmer groups. Corporate Farming implemented by Tani Mandiri farmer group is experimental independently, comes from the desire and willingness of farmers to be upgraded wich is jointly managed for the success of the full overlay mechanization program in 2015 on an area of 100 hectares. This study aims to 1) examine the use of full overlay mechanization in the implementation of CF attempt at Tani Mandiri Farmer Group Association and 2) examine management in the implementation of CF attempt at Tani Mandiri Farmer Group Association. The research was conducted using a descriptive method with a qualitative approach and a case study research design. The results showed that Tani Mandiri Farmer Group Association adopted the concept of CF by adjusting to the capabilities of both in terms of agricultural production facilities and human resources, so that it could not be said that they had fully implemented the whole concept of CF.